Direct ink writing of polyimide/bacterial cellulose composite aerogel for thermal insulation. (April 2023) - Ma, Zhuocheng; Xue, Tiantian; Wali, Qamar; Miao, Yue-E; Fan, Wei; Liu, Tianxi
Abstract: Polyimide (PI) aerogels are well known for their high porosity, low density, thermal insulation and outstanding mechanical strength, thus expected to be applied in aerospace vehicle, intelligent driving and batteries. However, currently most PI aerogels are fabricated through traditional molding process, seriously restricted their practical applications. Although some researches on 3D printing of PI aerogels have been reported, there are some critical restrictions in present work such as complex support structures, low porosity and high thermal conductivity resulting from high solid content in printed ink. Herein, we choose bacterial cellulose (BC) with high aspect ratio as rheological modifier to construct water-based polyamic acid (PAA)/BC ink with low solid content but high yield stress enough for direct ink writing (DIW). Due to the good printability and formability of PAA/BC ink, the PI/BC aerogel with various macrostructures can be easily printed. Owing to the orientation from printing, the obtained printed PI/BC aerogel shows lower shrinkage, lower thermal conductivity and enhanced mechanical properties compared with molded PI/BC aerogels. Such printed PI/BC aerogel is potentially to be applied as thermal insulators for designated products with specific complex structure in fields of buildings and petrochemical engineering. Graphical abstract: Image 1 Highlights: Bacterial Cellulose is applied as rheological modifier of PAA solution to form printable ink with low solid content. PI/BC aerogel is printed with low density and low thermal conductivity compared with molded PI/BC aerogel. Orientation occurs during printing, enhancing the tensile strength and modulus of printed PI/BC aerogel. PI/BC aerogel could be printed as coating of complex structures for thermal insulation.